OCM 2023 6th International Conference on Optical Characterization of Materials : Conference Proceedings March 22nd - 23rd, 2023 Karlsruhe | Germany - Beyerer, Jürgen; Längle, Thomas; Heizmann, Michael (KIT Scientific Publishing, 2023)
The state of the art in the optical characterization of materials is advancing rapidly. New insights have been gained into the theoretical foundations of this research and exciting developments have been made in practice, driven by new applications and innovative sensor technologies that are constantly evolving.The great success of past conferences proves the necessity of a platform for presentation, discussion and evaluation of the latest research results in this interdisciplinary field.